2016
DOI: 10.22267/rcia.153202.16
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de diferentes diodos emisores de luz (LEDs) unidos a trampas adhesivas amarillas para la captura de la mosca blanca Trialeurodes vaporariorum

Abstract: RESUMENTeniendo en cuenta que algunos adultos de insectos muestran preferencia a ciertas longitudes de onda, se ha considerado este comportamiento para desarrollar herramientas de monitoreo y estrategias de control de insectos plaga. Como ejemplo de ello, las tarjetas adhesivas amarillas han sido ampliamente usadas para monitorear población de moscas blancas a campo como invernadero. Este estudio tuvo como objetivo evaluar la efectividad de trampas adhesivas amarillas provistas con luces emitidas por diodos (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…However, in our field test, the yellow sticky card equipped with UV LED lights caught the least number of greenhouse whiteflies in a 24 h observation period. This weak attractiveness of the UV LED light was consistent with the results of some cage tests [14,16]. Yellow sticky cards alone were more attractive to greenhouse whiteflies than those supplemented with UV LED lights, both during the day and at night time.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, in our field test, the yellow sticky card equipped with UV LED lights caught the least number of greenhouse whiteflies in a 24 h observation period. This weak attractiveness of the UV LED light was consistent with the results of some cage tests [14,16]. Yellow sticky cards alone were more attractive to greenhouse whiteflies than those supplemented with UV LED lights, both during the day and at night time.…”
Section: Discussionsupporting
confidence: 85%
“…Some studies have shown that LED lights served as attractants [11][12][13][14][15] and increased the trapping efficacy of many insects, including greenhouse whiteflies, tobacco whiteflies, sweet potato whiteflies, thrips, and fungus gnats. However, most studies have been laboratory or confined cage studies, and field studies are still quite limited [16][17][18][19]. In this study, we used the greenhouse whitefly Trialeurodes vaporariorum (Westwood), an important pest worldwide, as a target insect to explore and evaluate the application potential of LED lights for the mass trapping of small diurnal insects in a greenhouse field test.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations